Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1063/1.475057
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of supercooling of a liquid on its overheating

Abstract: The nucleation process and the roles of structure and density fluctuations in supercooled liquid Fe Nucleation energetics during homogeneous solidification in elemental metallic liquids J. Appl. Phys.Heat capacity of tetrahydrofuran clathrate hydrate and of its components, and the clathrate formation from supercooled melt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…It has been found that a minimum superheating temperature of 40 K is required in order to achieve any undercooling prior to crystallization nucleation. This phenomenon is also observed in many magnetic texturing experiments [65]. In Table 3, the first Cu supercluster to be melted at θ = 0.033 in 600 s, corresponding to a superheating of 44.7 K, contains 13 atoms in perfect agreement with the observation.…”
Section: Analysis Of the Influence Of Cu Superheating Time On The Undsupporting
confidence: 76%
“…It has been found that a minimum superheating temperature of 40 K is required in order to achieve any undercooling prior to crystallization nucleation. This phenomenon is also observed in many magnetic texturing experiments [65]. In Table 3, the first Cu supercluster to be melted at θ = 0.033 in 600 s, corresponding to a superheating of 44.7 K, contains 13 atoms in perfect agreement with the observation.…”
Section: Analysis Of the Influence Of Cu Superheating Time On The Undsupporting
confidence: 76%
“…The findings of Goetz and his contemporaries appear to be related to a striking effect reported in modern calorimetric studies of resolidification of bismuth after heating slightly above melting [25,26]. These studies have not noted the possibility of such a relation, and have accordingly made no attempt to monitor crystal orientations.…”
mentioning
confidence: 55%
“…Thus, the orientational effects observed by Goetz can be expected only in samples exhibiting "equilibrium" resolidification. It should be noted that the studies quoted make conflicting claims regarding the reported transition: Aleksandrov and coworkers [25] report a sharp "phase transition" between "equilibrium" and "explosive" behaviors, regardless of heating and cooling rates (although the temperature associated with this transition differs between the earlier and the later publications); Tong and Shi [26] report a transient effect, with only "explosive" resolidification observed if the sample is held at temperatures above melting for an extended time. Clearly, some of the relevant parameters are not under sufficient experimental control to achieve reproducibility of the phenomena.…”
mentioning
confidence: 94%
“…The thermal history effect can be quantified by the relationship between liquid overheating (Δ T + ), which is measured by the difference between liquid temperature and the equilibrium melting point ( T 0 ), and liquid supercooling (Δ T − ), which is measured by the difference between T 0 and the temperature of solidification. Thus far, the dependence of Δ T − on Δ T + has been investigated in metals/semimetals (Bi, Sn, Ga) [2,3,4,5,11,14] and alloys [6,7,8,9,10,11]; typically Δ T − increases with an increase of Δ T + up to several to tens of degrees above T 0 . Despite the fundamental and technical importance, the underlying mechanism of this phenomenon in relation to the liquid structure and the kinetics of heterogeneous nucleation of solidification is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The cavity theory has been quantitatively validated by various experimental results [2,3,4,5], but it was considered to be not general, e.g., the dependence of Δ T − on Δ T + in Bi, Sn, SnSb and SnPb was found to be either continuous or discontinuous [10,11], which points to the evolution of transient short range order structures in the liquid state. Obviously, more investigations of the Δ T + -Δ T − relationship (thermal history effect) in metals and alloys are needed.…”
Section: Introductionmentioning
confidence: 99%